Incidence trends of lung and gastroenteropancreatic neuroendocrine neoplasms in Switzerland. (20th October 2020) - Alwan, Heba; La Rosa, Stefano; Andreas Kopp, Peter; Germann, Simon; Maspoli‐Conconi, Manuela; Sempoux, Christine; Bulliard, Jean‐Luc
Abstract: The incidence of neuroendocrine neoplasms (NENs) seems to increase worldwide. Long‐term, population‐based series that consider tumor differentiation are, however, sparse. We assessed the incidence trend of lung and gastroenteropancreatic (GEP) NENs according to the latest International Agency for Research on Cancer/World Health Organization classification over a 41‐year time period in two Swiss regions. All cases of lung and GEP NENs recorded in the Vaud and Neuchâtel Cancer Registries from 1976 to 2016 were included. NENs were stratified into well‐differentiated neuroendocrine tumors (NETs) and poorly differentiated neuroendocrine carcinomas (NECs). Changes in annual age‐standardized incidence rates were calculated for lung and GEP NETs and NECs by sex. Of 4, 141 patients diagnosed with NENs, 65% were men. The incidence of lung NETs among men and women increased by 3.9%/year (95% CI: −5.3, 14.1%) and 4.9%/year (0.1, 9.9%), respectively, between 1976 and 2016. The incidence of lung NECs decreased by 2.6%/year (−3.1, ‐1.8%) in men from 1985 to 2016 whereas it increased in women between 1976 and 1998 by 6%/year (4.2, 7.9%). For GEP NETs, a steady annual increase in incidence occurred between 1976 and 2016 with a magnitude of 1.7% (0.7, 2.7%) in men and 1.3% (0.5, 2.1%) in women. No significant trend in incidence of GEP NECs was found for both sexes. The incidence trends of lung NECs in men and women parallel changes in smoking prevalence in the population. Causes of the increase in incidence of GEP NETs are likely multifactorial. Our study supports the importance of evaluating the epidemiology of NENs by tumor differentiation. Abstract : Over the last four decades, the incidence trends of neuroendocrine lung neoplasms (NENs) parallel, in men and women, changes in smoking prevalence in the population. The steady increase in gastroenteropancreatic (GEP) NENs in both sexes is likely multifactorial but has not yet been fully elucidated.